2008
DOI: 10.1016/j.cognition.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Talker adaptation in speech perception: Adjusting the signal or the representations?

Abstract: Past research has established that listeners can accommodate a wide range of talkers in understanding language. How this adjustment operates, however, is a matter of debate. Here, listeners were exposed to spoken words from a speaker of an American English dialect in which the vowel /æ/ is raised before /g/, but not before /k/. Results from two experiments showed that listeners’ identification of /k/-final words like back (which are unaffected by the dialect) was facilitated by prior exposure to their dialect-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 23 publications
4
111
2
Order By: Relevance
“…A possible explanation is that each participant heard only one speaker. As listeners typically adapt very rapidly to a new speaker (e.g., Dahan, Drucker, and Scarborough, 2008), participants had probably already adapted to the speaker during the first block. Consequently, the differences between the speakers did not play a substantial role.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation is that each participant heard only one speaker. As listeners typically adapt very rapidly to a new speaker (e.g., Dahan, Drucker, and Scarborough, 2008), participants had probably already adapted to the speaker during the first block. Consequently, the differences between the speakers did not play a substantial role.…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear, however, which specific phenomena the listeners tuned in to. Dahan et al (2008) showed that listeners can tune in to regional variation of a given speaker's native language. In their study, listeners adapted to a regional phenomenon (the raising of the vowel /ae/ before /ɡ/, but not before /k/) which facilitates word recognition by reducing ambiguity in the initial part of words like bag and back.…”
Section: Discussionmentioning
confidence: 99%
“…That is, like Dahan et al (2008), we wanted to test listeners' ability to adjust to naturally-occurring idiosyncrasies of a speaker, but unlike them we were interested in stylistic rather than in geographical variation as the source of the idiosyncrasies. Geographical variation is tied to groups of speakers (e.g.…”
Section: Speaker-specific Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative possibility, however, is that learning reflects the tuning of transformational processes that enable the listener to more efficiently translate ambiguous input to the (unshifted) representation. Dahan, Drucker, and Scarborough (2008) addressed this question by looking at the effect that exposure to one nonstandard pronunciation (e.g., raised [ ] before / /, as in some speakers' pronunciations of the word bag) has on subsequent perception of a different, related pronunciation (e.g., standard [ ] before / /, as in the word back). Using eyetracking as their measure, Dahan et al found that exposure to a speaker with a raised vowel (in words such as bag) caused listeners to be more likely to interpret the standard pronunciation / / as the onset of / / (as opposed to finding the onset ambiguous between / / and / /, as they would before exposure).…”
Section: Theme II Perceptual Learning As Phonetic Retuningmentioning
confidence: 99%